CONTEMPORARY MASS CHOREOGRAPHIES IN ITALY: VIRGILIO SIENI’S «AGORAS» AND «CIVIC WALKS» - Mazzaglia , Rossella (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
Marseille 2013: more than a hundred amateur performers from different areas of the Mediterranean conjoin in site-specific dances claiming a multicultural polis. Short after in Italy, several cities become venues of mass choreographies enacting «agoras» and «civic walks» in iconic sites. The artist beyond these secular rituals is Virgilio Sieni, a leading Italian choreographer, and a model case in Italy for performances with amateur dancers. Selected case studies from his productions will be compared to other forms of participatory art such as theatre and analyzed as «community figures» (Rancière), and «assemblies of bodies» (Butler) ultimately elucidating forms of cultural resilience to the political Italian scene of the pre-pandemic years.